Ho:SSO solid-state saturable-absorber Q switch for pulsed Ho:YAG laser resonantly pumped by a Tm:YLF laser. (November 2018) - Yang, Xiao-tao; Mu, Yan-long; Zhao, Ning-bo
Highlights: We report a passively Q-switch Ho:YAG laser modulated by a Ho:Sc2 SiO5 saturable absorber for the first time. The maximum peak power of the passively Q-switch Ho:YAG laser is 1.53 kW, and the maximum repetition rate is 42.1 kHz. The minimum pulsed duration is 48 ns. Abstract: A Ho:SSO crystal was employed as an efficient saturable absorber Q switch for the pulsed Ho:YAG laser for the first time. The characteristics of the passive Q-switch Ho:YAG laser were studied with different incident pump power and different laser energy density around the Ho:SSO. The single pulsed energy varied from 8.3 μJ to 76.6 μJ with the increasing of the incident power from 2.2 W to 8.2 W. The maximum repetition rate was 42.1 kHz, and the minimum pulsed duration was 48 ns. The maximum single-pulse peak power was 1.53 kW. The output center wavelength shifted from 2090.1 nm (the continuous-wave mode) to 2091.3 nm (the passive Q-switch mode).